Sanguinarine Induces Apoptosis Pathway in Multiple Myeloma Cell Lines via Inhibition of the JaK2/STAT3 Signaling - Sabah Akhtar (5809925) (2019)
Sanguinarine (SNG), a benzophenanthridine alkaloid, has displayed various anticancer abilities in several vivo and in vitro studies. However, the anticancer potential of SNG is yet to be established in multiple myeloma (MM), a mostly incurable malignancy of plasma cells. In this study, we aimed to investigate the potential anti-proliferative and pro-apoptotic activities of SNG in a panel of MM cell lines (U266, IM9, MM1S, and RPMI-8226). SNG treatment of MM cells resulted in a dose-dependent decrease in cell viability through mitochondrial membrane potential loss and activation of caspase 3, 9, and cleavage of PARP. Pre-treatment of MM cells with a universal caspase inhibitor, Z-VAD-FMK, prevented SNG mediated loss of cell viability, apoptosis, and caspase activation, confirming that SNG-mediated apoptosis is caspase-dependent. The SNG-mediated apoptosis appears to be resulted from suppression of the constitutively active STAT3 with a concomitant increase in expression of protein tyrosine phosphatase (SHP-1). SNG treatment of MM cells leads to down-regulation of the anti-apoptotic proteins including cyclin D, Bcl-2, Bclxl, and XIAP. In addition, it also upregulates pro-apoptotic protein, Bax. SNG mediated cellular DNA damage in MM cell lines by induction of oxidative stress through the generation of reactive oxygen species and depletion of glutathione. Finally, the subtoxic concentration of SNG enhanced the cytotoxic effects of anticancer drugs bortezomib (BTZ) by suppressing the viability of MM cells via induction of caspase-mediated apoptosis. Altogether our findings demonstrate that SNG induces mitochondrial and caspase-dependent apoptosis, generates oxidative stress, and suppresses MM cell lines proliferation. In addition, co-treatment of MM cell lines with sub-toxic doses of SNG and BTZ potentiated the cytotoxic activity. These results would suggest that SNG could be developed into therapeutic agent either alone or in combination with other anticancer drugs in MM. Other Information Published in: Frontiers in Oncology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fonc.2019.00285